2021
DOI: 10.1158/1940-6207.capr-20-0650
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Polyclonal Antibody Stimulator (PAS) Prevents Pancreatic Carcinogenesis in the KRAS Mouse Model

Abstract: The incidence of pancreatic cancer is increasing significantly and will soon become the second leading cause of cancer-related deaths in the United States. We have previously shown that the gastrointestinal peptide gastrin, which is only expressed in the fetal pancreas and not in the adult pancreas, is activated during pancreatic carcinogenesis where it stimulates growth in an autocrine fashion. In this investigation, we used transgenic LSL-KrasG12D/+; P48-Cre mice that develop precancerous pancreatic intraepi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The decreased fibrosis observed with PAS therapy may help to explain the synergy previously found with gemcitabine. PAS vaccination in a precancerous KRAS murine model demonstrated that PAS not only decreases pancreatic fibrosis and alters the immune cell signature of the tumor microenvironment but that it also decreases proliferation and progression on precancerous PanIN lesions preventing pancreatic cancer ( 45 ). The data are compelling for PAS to return to the clinic with a much better understanding of how to use the product.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased fibrosis observed with PAS therapy may help to explain the synergy previously found with gemcitabine. PAS vaccination in a precancerous KRAS murine model demonstrated that PAS not only decreases pancreatic fibrosis and alters the immune cell signature of the tumor microenvironment but that it also decreases proliferation and progression on precancerous PanIN lesions preventing pancreatic cancer ( 45 ). The data are compelling for PAS to return to the clinic with a much better understanding of how to use the product.…”
Section: Discussionmentioning
confidence: 99%